(untitled) (Fiep Bulletin - online, 2016)
This study aimed to analyze the distortion of body image and their degrees of development in adolescents of both sexes of the state of Rondonia. Therefore, in the study sample consisted of 93 adolescents, 42 males and 51 females, aged between 11 and 16, all from one school to private school, the Centro Educational Sao Paulo , located the city of Ji-Paraná, Rondonia state. To obtain data regarding the presence of distortion of body self-image and their degree of development was applied to the Body Shape Questionnaire (BSQ), in its translated version and validity for Portuguesa analysis of prevalence data was performed using Excel (2000). Through data analysis, we determined that more than half of both groups, 65% of female adolescents and 74% male, a prevalence of distorted body image in varying degrees. When comparing both groups, can be seen that although males had a greater prevalence of distorted body self-image, this was identified with mild, while in girls was more prevalent in moderate to severe levels of greater concern. Therefore, the study found that sex is not decisive for the presence of distortion of body self-image. However, the severity of their presence seems to be more common among adolescent girls of school age. Recommended that preventive measures be taken in the school through the SDSS population of students, as well as psychological and a physical education professional to guide young people to practice physical activity in ahealthyway.